2011
DOI: 10.1510/icvts.2010.242750
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the patterns, presentation and management of penetrating chest trauma patients at a level II trauma centre in Southern Pakistan over the last two decades

Abstract: Penetrating chest trauma can be used as an indicator of violence in the country. We aimed to look at the changes in its incidence and management at a major trauma centre in the country. We also wanted to look at any effect of prehospital time on surgical intervention and outcome of the victim. In this retrospective descriptive study, we observed the presentation and management of 191 penetrating chest injury patients at a level II trauma hospital in Pakistan in the last 20 years. The study sample was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 11 publications
3
18
1
3
Order By: Relevance
“…Res. 4(10), 1318-1321 1319 Penetrating thoracic trauma is mostly attributed to violence and has a higher mortality rate than blunt trauma (2,6). It is more common in men due to their propensity to violence and the mechanism of injury is usually a gunshot wound or stab wound.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 4 more Smart Citations
“…Res. 4(10), 1318-1321 1319 Penetrating thoracic trauma is mostly attributed to violence and has a higher mortality rate than blunt trauma (2,6). It is more common in men due to their propensity to violence and the mechanism of injury is usually a gunshot wound or stab wound.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…It is more common in men due to their propensity to violence and the mechanism of injury is usually a gunshot wound or stab wound. Early recognition and timely treatment of life-threatening injuries, better resuscitative techniques, preoperative care, and elective surgical procedures can significantlyaffect outcomes in these patients (2). Studies have shown chest tube thoracostomy to be the primary modality for managing nonmediastinal, peripheral chest injury, with a very low incidence of thoracotomy (2,7).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 3 more Smart Citations